2011
DOI: 10.1002/ejlt.201000485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ferric chloride on thermal degradation of γ‐oryzanol and oxidation of rice bran oil

Abstract: The kinetics of g-oryzanol degradation in antioxidant-stripped rice bran oil were investigated at 1808C for 50 h. Ferric chloride was added to the oil at different concentrations (0, 2.5, 5.0, and 7.5 mg/kg-oil) to determine the degradation reaction rate of g-oryzanol and the extent of lipid oxidation (peroxide value and p-anisidine value). It was found that the losses of g-oryzanol and its four components (cycloartenyl ferulate, 24-methylene cycloartanyl ferulate, campesteryl ferulate, and b-sitosteryl ferula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…γ-Oryzanol and its components exhibited conformity to the first-order kinetic model at different thermal treatment temperatures ( R 2 > 0.9) (Table S1). Similar observations have been documented in previous studies, which found that the degradation of γ-oryzanol during heating followed first-order kinetics. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…γ-Oryzanol and its components exhibited conformity to the first-order kinetic model at different thermal treatment temperatures ( R 2 > 0.9) (Table S1). Similar observations have been documented in previous studies, which found that the degradation of γ-oryzanol during heating followed first-order kinetics. , …”
Section: Resultssupporting
confidence: 91%
“…Similar observations have been documented in previous studies, which found that the degradation of γ-oryzanol during heating followed first-order kinetics. 11,35 According to the results shown in Table 2, it can be observed that with increasing temperature, the thermal degradation rate constant (K) of γ-oryzanol and its four components increased while the half-life (t 1/2 ) decreased. These results indicated that higher temperatures have a greater impact on the stability of γ-oryzanol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Khuwijitjaru, P. et al . found that the loss of γ-oryzanol and its four components (cycloartenyl ferulate, 24-methylene cycloartanyl ferulate, campesteryl ferulate, and b-sitosteryl ferulate) could be described by a first-order kinetics model 18 . Similarly, Castaneda, E. J. L. et al .…”
mentioning
confidence: 99%